Principales similitudes y diferencias entre los sistemas presupuestales de la republica de Argentina y la república de Colombia (2013)
The Colombian Budgetary System has specific characteristics that make it up as a Budgetary System different from other systems in Latin America, and also has a number of similar characteristics that make it similar to other systems. The Republic of Argentina as Colombia has configured it ́s Budget System under the influence of political and economic events wich have had an impact as well on other Latin American countries such as Colombia. This allows to relate the similarities and differences which arise structural and functional in order to determine an overview of Budgetary System of the Republic of Colombia in relation to the Budgetary System of the Republic of Argentina.